1983
DOI: 10.1161/01.res.53.1.24
|View full text |Cite
|
Sign up to set email alerts
|

Renal responses of the cardiac-denervated nonhuman primate to blood volume expansion.

Abstract: SUMMARY. Experiments were performed to determine whether total, specific cardiac denervation affects the renal responses of the nonhuman primate to acute inrravascular volume expansion. Adult male Macaca fascicularis monkeys underwent chronic intrapericardial cardiac denervation or sham surgery. After a 14-to 30-day recovery period, each animal was anesthetized with sodium pentobarbital and estimated blood volume was volume-expanded 20% with 6% dextran in isotonic saline. Control renal excretory function did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1985
1985
1995
1995

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Although the role of atrial volume receptors in the control of ADH secretion has been demonstrated in dogs (Gauer er al., 1970;Gauer & Henry, 1976, 1983, data from studies using the non-human primate have suggested that these receptors may play a small role in regulating blood volume. Furthermore, cervical vagotomy (Gilmore et al, 1979) or complete, selective cardiac denervation (Peterson & Jones, 1983) failed to attenuate the diuretic response to volume expansion or water immersion in the monkey, although ADH levels were not measured in these animals. 1976;Linden, 1976;Fater et al, 1982) failed to elicit any renal effects in either the anaesthetized or conscious monkey (Gilmore & Zucker, 1978b;Peterson ef al., 1980Peterson ef al., , 1983Cornish & Gilmore, 1982).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the role of atrial volume receptors in the control of ADH secretion has been demonstrated in dogs (Gauer er al., 1970;Gauer & Henry, 1976, 1983, data from studies using the non-human primate have suggested that these receptors may play a small role in regulating blood volume. Furthermore, cervical vagotomy (Gilmore et al, 1979) or complete, selective cardiac denervation (Peterson & Jones, 1983) failed to attenuate the diuretic response to volume expansion or water immersion in the monkey, although ADH levels were not measured in these animals. 1976;Linden, 1976;Fater et al, 1982) failed to elicit any renal effects in either the anaesthetized or conscious monkey (Gilmore & Zucker, 1978b;Peterson ef al., 1980Peterson ef al., , 1983Cornish & Gilmore, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…According to the Henry-Gauer hypothesis (Gauer el al., 1970;Gauer & Henry, 1983), the sudden shift in fluids from the legs and abdomen into the chest and head leads to stretch of low pressure receptors (located in the atrium and/or pulmonary circulation) as evidence of an increase in total circulating blood volume. Recently the importance of the proposed Henry-Gauer atrial receptors in control of ADH responses to acute blood volume shifts in man have been challenged by observations that vagotomized non-human primates exhibit significant diuresis during water immersion or volume expansion (Gilmore & Zucker, 1978a;Peterson & Jones, 1983). Most of the evidence supporting this hypothesis has come from studies using the dog (Gauer & Henry, 1976;Linden, 1976;Donald & Shepherd, 1978), where the receptors have been shown to be primarily located in the atrial wall and the ADH response to be abolished by vagotomy.…”
Section: Introductionmentioning
confidence: 99%
“…The absence of such compensatory adjustments is also consistent with the apparent lack of functional arterial baroreceptors in this species (19). In contrast, arterial pressure changes are not observed following cardiac denervation in dogs (23,24) or in a nonhuman primate (25).…”
Section: Asotocin In Chickensmentioning
confidence: 98%
“…For example, selective ablation of volume receptor neural pathways such as thoracic dorsal rhizotomy (10), vagotomy-sinoaortie denervation (10), thoracic sympathectomy (3) or cardiac denervation (24) does not attenuate the renal excretory responses of the anesthetized monkey to volume expansion. However, this failure of selective denervations to affect these responses could be due to these mechanisms being functionally redundant.…”
Section: Introductionmentioning
confidence: 99%